Cover Picture: An Efficient Conjugation Approach for Coupling Drugs to Native Antibodies via the PtII Linker Lx for Improved Manufacturability of Antibody–Drug Conjugates (Angew. Chem. Int. Ed. 6/2021). Issue 6 (1st February 2021) - Merkul, Eugen; Muns, Joey A.; Sijbrandi, Niels J.; Houthoff, Hendrik‐Jan; Nijmeijer, Bart; van Rheenen, Gerro; Reedijk, Jan; van Dongen, Guus A. M. S.
Abstract : Efficient His conjugation towards Lx ‐ADCs was achieved by an unprecedented coupling of platinum(II)‐based drug‐bearing precursors to native mAbs. This novel and easily scalable bioconjugation approach was realized by the addition of simple iodide salts such as NaI, as described by Eugen Merkul et al. in their Research Article on page 3008 . Cover designed by Tom van Rheenen.